Definite article usage across varieties of English - Abdul Wahid, Mohd Ridwan (Wiley-Blackwell, 2013)
This paper seeks to explore the extent of definite article usage variation in several varieties of English based on a classification of its usage types. An annotation scheme based on Hawkins and Prince was developed for this purpose. Using matching corpus data representing Inner Circle varieties and Outer Circle varieties, analysis was made on approximately 14,000 tokens of the in private dialogue, academic writing and reportage. It was found that the different percentages of usage types in the three registers across the varieties were statistically significant. However there was no clear trend that could be observed in either group. The trends of the varieties, collectively or individually, were so unpredictable that in the end there was no evidence of an overall trend. Register, consistent with Biber et al.’s claim, was instead found to be a better predictor of the usage types of the in the varieties. The classification of the varieties as either Inner or Outer Circle was therefore shown to be less influential in the quantitative variation of the morpheme than previously thought. Nevertheless, a subsequent qualitative analysis showed that the structural and situational categories in the Outer Circle did contain a number of marked usages of the,presenting themselves as the clearest cases of variation in the data.